Functional results of shoulders Neer’s prosthesis for four part fracture dislocation of shoulder - Abdul Aziz, Ansari Muqtadeer; Rathod, Pratik; Patel, Altamash (International Journal of Research in Orthopaedics, 2021)
Background: Objective was to study the clinical and functional outcome of shoulder hemi-arthroplasty using Neer’s prosthesis in four part fracture dislocation of shoulder. Methods: The study was conducted on patients who underwent shoulder hemi-arthroplasty using Neer’s prosthesis for four part fracture dislocation of shoulder in Department of Orthopaedics, GMCH Aurangabad from January 2020 to January 2021. The patients were assessed clinically and functionally using Shoulder range of motion, Visual Analog Scale (VAS), American Society of shoulder and elbow (ASES) score and Constant-Murley score and radiological assessment at 3, 6 and 12 months. Results: At one year follow up of 30 patients, no loosening or dislocation of prosthesis was detected, and mean forward elevation of 129.33o (90o - 150o), mean external rotation of 26.7o (18o – 34o), mean internal rotation of 47.86o (33o-58o), the mean ASES score of 79.46 (range 68-88), the mean VAS score of 1.5 (range 1-3) and mean Constant-Murley score of 82.9 (range 72-94) were achieved. 1 patient developed axillary nerve injury which recovered 6 weeks after surgery and 1 diabetic patient developed superficial infection which healed with antibiotics. Conclusions: Hemiarthroplasty with Neer’s prosthesis can be utilized in four part fracture dislocations of humerus with poor bone stock risking avascular necrosis of head and screw cut out with satisfactory outcome.